Benchmarked performance charts using principal components analysis to improve the effectiveness of feedback for audit data in HIV care - Michael, Skevi; Gompels, Mark; Sabin, Caroline; Curtis, Hilary; May, Margaret T. (BMC health services research, 2017)
Background Feedback tools for clinical audit data that compare site-specific results to average performance over all sites can be useful for quality improvement. Proposed tools should be simple and clearly benchmark the site’s performance, so that a relevant action plan can be directly implemented to improve patient care services. We aimed to develop such a tool in order to feedback data to UK HIV clinics participating in the 2015 British HIV Association (BHIVA) audit assessing compliance with the 2011 guidelines for routine investigation and monitoring of adult HIV-1- infected individuals. Methods HIV clinic sites were asked to provide data on a random sample of 50–100 adult patients attending for HIV care during 2014 and/or 2015 by completing a self-audit spreadsheet. Outcomes audited included the proportion of patients with recorded resistance testing, viral load monitoring, adherence assessment, medications, hepatitis testing, vaccination management, risk assessments, and sexual health screening. For each outcome we benchmarked the proportion for a specific site against the average performance. We produced performance charts for each site using boxplots for the outcomes. We also used the mean and differences from the mean performance to produce a dashboard for each site. We used principal components analysis to group correlated outcomes and simplify the dashboard. Results The 106 sites included in the study provided information on a total of 7768 patients. Outcomes capturing monitoring of treatment of HIV-infection showed high performance across the sites, whereas testing for hepatitis, and risk assessment for cardiovascular disease and smoking, management of flu vaccination, sexual health screening, and cervical cytology for women were very variable across sites. The principal components analysis reduced the original 12 outcomes to four factors that represented HIV care, hepatitis testing, other screening tests, and resistance testing. These provided simplified measures of adherence to guidelines which were presented as a 4 bar dashboard of performance. Conclusion Our dashboard performance charts provide easily digestible visual summaries of locally relevant audit data that are benchmarked against the overall mean and can be used to improve feedback to HIV services. Feedback from clinicians indicated that they found these charts acceptable and useful.